A comparison of muscle activity of the dominant and non-dominant side of the body during low versus high loaded bench press exercise performed to muscular failure. (February 2021) - Krzysztofik, Michal; Jarosz, Jakub; Matykiewicz, Patryk; Wilk, Michal; Bialas, Marcin; Zajac, Adam; Golas, Artur
Abstract: The main aim of the study was to compare the peak surface electromyography (sEMG) amplitude of muscles during low and high loaded bench press exercises performed to muscular failure on the dominant and non-dominant body side. Ten resistance-trained healthy males with at least six-year experience in resistance training (27.7 ± 5.6 years, 81.1 ± 5.8 kg and 175.3 ± 5.2 cm, bench press one-repetition maximum [1RM] = 98.9 ± 7.1 kg) performed the bench press at 50% and at 90%1RM. The differences in peak sEMG amplitude between body-sides and the external loads were recorded for the pectoralis major (PM), anterior deltoid (AD), and the long head of the triceps brachii (TB) during each attempt. A two-way repeated-measures ANOVAs revealed statistically significant main effect of side for AD (p < 0.001) and TB (p < 0.001) but not for PM (p = 0.168) and a significant main effect of load for TB (p < 0.001) but not for AD and PM (p = 0.229; p = 0.072; respectively). The post-hoc analysis for the main effect of side showed significantly higher peak sEMG amplitude for the dominant side compared to the non-dominant side for AD and TB at 50%1RM and 90%1RM (p < 0.001; all) with no statistically significant differences for PM (p = 0.187; p = 0.155; both loads). The post-hoc analysis for the main effect of load for TB revealed a significantly higher peak sEMG amplitude at 90%1RM compared to the 50%1RM (p = 0.009). The obtained results indicate that regardless of the external load, the peak sEMG activity of the AD, PM, and TB during the bench press exercise performed to muscular failure was higher on the dominant body-side.